A mutiny in time - Dashner, James, 1972- (Infinity ring ;, 2012)
Time has gone wrong, and best friends Dak Smyth and Sera Froste, together with the young Hystorian Riq, must use the infinity ring to travel back to one of the Great Breaks--a mutiny on the Santa María--to correct history and defeat the SQ.